The Relationship Between Helicobacter Pylori Infection And Childhood Idiopathic Thrombocytopenic Purpura - Abbas, Sawsan S.; Hadi, Tariq M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Idiopathic thrombocytopenic purpura , a disorder characterized by autoantibody mediated platelets destruction causing decreased number of circulating platelets manifest as bleeding tendency. Since the discovery of Helicobacter pylori (H. pylori ) several studies have been published concerning a hypothetical role of this bacteria in idiopathic thrombocytopenic purpura.Aim of the study: Evaluate the pathogenic correlation between H.pylori infection and idiopathic thrombocytopenic purpura.Patients and Method: A cross sectional study was done on 30 cases of idiopathic thrombocytopenic purpura admitted to the Pediatric Hemato-Oncology unit in ALKadhimiyia Teaching Hospital and 20 cases of sex and age matched healthy children as a control to determine the relation between H. pylori infection and idiopathic thrombocytopenic purpura. The peak age for idiopathic thrombocytopenic purpura was between ( 6-10 years) of age, (43.33%). Male : female ratio equal to 2:1 . ELIZA test was used to measure the serum IgG antibody titer against H. pylori , 5 cases of idiopathic thrombocytopenic purpura was found to be positive for H.pylori (16.67%)while the test was negative in all of the control group (100%) ,Results: a result which is statistically highly s i g n i f i c a n t , p - value